Microfluidic platform for the real time measurement and observation of endothelial barrier function under shear stress - Lewis, Daniel M. (Biomicrofluidics, 2018)
Electric cell-substrate impedance sensing (ECIS) is a quickly advancing field to measure the barrier function of endothelial cells. Most ECIS systems that are commercially available use gold electrodes, which are opaque and do not allow for real-time imaging of cellular responses. In addition, most ECIS systems have a traditional tissue culture Petri-dish set up. This conventional set-up does not allow the introduction of physiologically relevant shear stress, which is crucial for the endothelial cell barrier function. Here, we created a new ECIS micro-bioreactor (MBR) that incorporates a clear electrode made of indium tin oxide in a microfluidic device. Using this device, we demonstrate the ability to monitor the barrier function along culture of cells under varying flow rates. We show that while two cell types align in the direction of flow in responses to high shear stress, they differ in the barrier function. Additionally, we observe a change in the barrier function in response to chemical perturbation. Following exposure to EDTA that disrupts cell-to-cell junctions, we could not observe distinct morphological changes but measured a loss of impedance that could be recovered with EDTA washout. High magnification imaging further demonstrates the loss and recovery of the barrier structure. Overall, we establish an ECIS MBR capable of real-time monitoring of the barrier function and cell morphology under shear stress and allowing high-resolution analysis of the barrier structure.